Peningkatan Pemahaman dan Kesadaran Gizi Melalui Edukasi Isi Piringku pada Murid SD Negeri 13 Ampenan Kota Mataram - Jauda Avaro Zufaru; Annisa Makarima Ahlaq; Nadine Desvita Alifia Putri; Sabrina Mawadathun Salsabila; Lalu Abdullah Rafi Asyari; Yoga Adiguna; Zaky; Agus Kurnia (Aksi: Jurnal Pengabdian Masyarakat, 2025)
Balanced nutrition is a crucial aspect of supporting children’s physical and cognitive growth while maintaining overall health. Nutritional imbalances, whether malnutrition or obesity, remain global issues, including in Indonesia. Early education on the importance of healthy eating habits is a strategic step in building community awareness about nutrition. This study was conducted at SD Negeri 13 Ampenan, aiming to improve the understanding of 5th-grade students regarding balanced nutrition through the “Isi Piringku” program. The methods involved a pre-test to assess students’ initial knowledge, delivery of educational material through engaging visual presentations, and an educational quiz in the form of a team-based competition to evaluate understanding. The results showed a significant increase in students’ comprehension, with most answering questions more accurately after the session. The interactive approach created an enjoyable and participatory learning atmosphere, fostering students’ awareness of the importance of nutrition. This activity not only positively impacted students’ nutrition literacy but also contributed to the achievement of Sustainable Development Goal (SDG) number 2, which focuses on improving community nutrition quality.